La enseñanza de las lenguas indígenas en Costa Rica - Carmen Rojas-Chaves (Universidad Nacional, Costa Rica, 2002)
In Costa Rica there are six indigenous languages which currently are becoming weaker due to the so-called "unified nation" with one language and one culture. Due to this situation, Costa Rica has ratified international agreements to conserve and spread autochthonous languages and cultures, along with promoting the education of indigenous children. The Program for the Teaching of Indigenous Languages in our country is trying to develop a way to transfer and recover cultural elements in spite of administrative, legal, mental, and cultural obstacles to cultural diversity.